1999
DOI: 10.1074/jbc.274.40.28067
|View full text |Cite
|
Sign up to set email alerts
|

B-myb Is Required for Inner Cell Mass Formation at an Early Stage of Development

Abstract: The myb gene family has three members, c-myb, A-myb, and B-myb, which have distinct expression patterns. Analyses of c-myb and A-myb mutant mice have indicated that c-myb and A-myb are important for hematopoiesis and spermatogenesis, respectively. However, there has been no evidence for a role for B-myb in development. To examine the role of B-myb in development, we generated B-myb-deficient mice by gene targeting. Although the heterozygous mutants were healthy, the homozygous mutants died at an early stage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
122
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(130 citation statements)
references
References 42 publications
7
122
1
Order By: Relevance
“…These WISH results confirmed this microarray-based finding. It is reported that Mybl2 −/− mice die at around E4.5 -E6.5 and in vitro culture of Mybl2 −/− blastocyst indicates that Mybl2 is required for ICM formation (Tanaka et al, 1999). The ICM-predominant expression of Mybl2 is thus consistent with this null phenotype.…”
Section: All Stage Analysis Of Selected Genesmentioning
confidence: 59%
“…These WISH results confirmed this microarray-based finding. It is reported that Mybl2 −/− mice die at around E4.5 -E6.5 and in vitro culture of Mybl2 −/− blastocyst indicates that Mybl2 is required for ICM formation (Tanaka et al, 1999). The ICM-predominant expression of Mybl2 is thus consistent with this null phenotype.…”
Section: All Stage Analysis Of Selected Genesmentioning
confidence: 59%
“…B-Myb-null mutant mice die at E4.5-6.5 due to failure of the inner cell mass to grow (Tanaka et al, 1999). Although the precise cause of this lethality is not known, evidence is emerging that B-Myb depletion in mouse ES cells (the in vitro counterpart of the inner cell mass) results in mitotic failure (Tarasov et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This data imply that a large fraction of the human population is carrier of B-MYB alleles that might be associated with a reduced risk of developing neoplastic disease. Oncogene (2008Oncogene ( ) 27, 2929Oncogene ( -2933doi:10.1038/sj.onc.1210947;published online 19 November 2007 Keywords: transcription; neuroblastoma; colon cancer; leukaemia; apoptosis B-MYB is a putative proto-oncogene required for mammalian development and involved in cell proliferation and survival (Oh and Reddy, 1999;Tanaka et al, 1999;Sala, 2005). Although there is still no evidence of its direct involvement in human cancer, several studies have revealed that B-MYB is either amplified or overexpressed in different human malignancies, while its expression in neuroblastoma patients correlates with poor survival (Raschella et al, 1999;Forozan et al, 2000;Tanner et al, 2000;Bar-Shira et al, 2002).…”
mentioning
confidence: 99%